Kinetika reaksi heterogen etanolisis minyak jarak kepyar (Ricinus communis) dengan katalisator zeolit klinoptilolit - Ratna Sri Harjanti; Sarto Sarto (Jurnal Rekayasa Proses, 2009)
Castor oil of Ricinus communis has potential as a raw material for biodiesel synthesis through catalytic alcoholysis process. Clinoptilolite type natural zeolite is one of solid catalysts that can be used in the alcoholysis process. In the present work, the alcoholysis was carried out in an autoclave reactor equipped with manometer, thermometer, sampling valve, and heating element. The reaction occurred at elevated temperatures with the use of clinoptilolite as a solid catalyst. The experimental data indicated that in a certain reaction time range, an increase in temperature and autoclave rotation speed lead to the increase of reaction conversion. Calculation results showed that the overall reaction rate was controlled by chemical reaction at the catalyst surface. The optimum condition of the alcoholysis process was obtained at reaction time of 60 minutes, temperature of 120C and autoclave rotation of 110 rpm with the use of alcohol-oil ratio of 12.56 mgek / mgek and 2.56% (w/w) catalyst. At the optimum condition, the conversion could reach as high as 0.73. The obtaining esters had a viscosity of 8.0 cst, -16.6°F pour point, 215°F flash point, ASTM color of 1, and heating value of 19,119 Btu/lb.